2016
DOI: 10.1080/01459740.2016.1173691
|View full text |Cite
|
Sign up to set email alerts
|

Ways of Doing: Restorative Practices, Governmentality, and Provider Conduct in Post-Apartheid Health Care

Abstract: In this article, we consider the conduct of post-apartheid health care in a policy context directed toward entrenching democracy, ensuring treatment-adherent patients, and creating a healthy populace actively responsible for their own health. We ask how tuberculosis treatment, antiretroviral therapy, and maternal services are delivered within South Africa's health system, an institutional site of colonial and apartheid injustice, and democratic reform. Using Foucauldian and post-Foucauldian notions of governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Updated findings . New studies added further examples that confirmed negative experiences at HIV clinics [ 31 , 32 , 45 , 48 , 49 , 52 , 55 , 57 , 60 , 79 ]. Physical space and layout of HIV clinics is not optimal due to poor signage and poorly laid out waiting areas (inside and outside the clinic) which do not offer PLHIV the privacy they desire.…”
Section: Resultsmentioning
confidence: 99%
“…Updated findings . New studies added further examples that confirmed negative experiences at HIV clinics [ 31 , 32 , 45 , 48 , 49 , 52 , 55 , 57 , 60 , 79 ]. Physical space and layout of HIV clinics is not optimal due to poor signage and poorly laid out waiting areas (inside and outside the clinic) which do not offer PLHIV the privacy they desire.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the working conditions at the MSF run hospitals may, even when congested, be of higher quality than in governmental hospitals within fragile, resource constrained healthcare systems; regarding resources, leadership, accountability, teamwork, guidance and transparency. Furthermore, compared to busy low-resource hospitals in East Africa with workloads similar to the high-volume month, the quality of care provided at these MSF run hospitals is much higher, and the intra-hospital stillbirth rates of 2.3-9.7 much lower [20,[23][24][25][26][27]. This may in itself be a positive driver among staff to keep providing quality care even when working 50% above capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Health care providers must take time to understand and engage with the patients during clinical consultations or treatment. Recent studies have revealed that patients are happier when involved in their own care (Harris et al, 2016). However, providers' inability to engage patients in discussing about their care may not be an individual problem; rather, it is a reflection of how the health care system is structured or functions (Valentijn et al, 2013).…”
Section: Discussionmentioning
confidence: 99%